Optimization of Development Funds to Achieve Dynamic Sustainable SME's - Feni Astuti (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
Micro, Small and Medium Enterprises (MSMEs) are the community-based business sector that has a strategic role in the economy and has a positive effect on social impacts through creating jobs and improving people's lives. With a total of 6,140 MSME players registered in 2020, Bandung City is one of the regions in West Java Province that is participating in developing this business sector. This is supported by the availability of the MSMEs Development Fund to create sustainable MSMEs in the city of Bandung. In realizing dynamic sustainable micro, small, medium enterprises in Bandung, the government, in this case the Office of Cooperatives, Micro, Small and Medium Enterprises, needs to use the existing budget optimally. This study aims to find out how to optimize the MSME Development Fund in the context of dynamic sustainable micro, small, medium enterprises in the Cooperative Office, Micro, Small, and Medium Enterprises in Bandung City. The research method used is a descriptive study with a qualitative approach. While the data collection technique is done through structured interview, observation, documentation, and literature study. Data analysis techniques are performed, namely data reduction, data display, and conclusion drawing, which is then tested for validity using data triangulation. The results showed that the development of MSMEs carried out by the Department of Cooperatives, Micro, Small and Medium Enterprises has not yet reached a sustainable stage. This is because there are two dimensions of dynamic sustainable micro, small, medium enterprises that have not been fulfilled.